Thermodynamic re-assessment of the Fe-Gd and Fe-Sm binary systems. (September 2017) - Chen, X.L.; Wang, J.; Chen, T.L.; Lin, X.D.; Rong, M.H.; Rao, G.H.; Zhou, H.Y.
Abstract: The Fe-Gd and Fe-Sm binary systems were re-assessed thermodynamically using the CALPHAD method based on the critical evaluation of previous optimizations and available experimental information in the published literature. The solution phases including liquid, fcc-Fe, bcc-Fe, bcc-Gd, hcp-Gd, bcc-Sm, hcp-Sm and rhombohedral-Sm, were described by the substitutional solution model and their excess Gibbs energies were expressed with the Redlich-Kister polynomial. The intermetallic compounds, α-Fe17 Gd2, β-Fe17 Gd2, Fe23 Gd6, Fe3 Gd, Fe2 Gd, Fe17 Sm2, Fe3 Sm and Fe2 Sm, were modeled as stoichiometric compounds due to their narrow homogeneity ranges. Self-consistent thermodynamic parameters to describe Gibbs energies of various phases in the Fe-Gd and Fe-Sm binary systems were obtained finally. The calculated results in this work are in good agreement with the reported phase equilibria and thermodynamic properties. Highlights: The Fe-Gd and Fe-Sm binary systems were assessed using CALPHAD method. Self-consistent thermodynamic parameters of these two binary systems were obtained. The calculation results agree well with phase equilibria and thermodynamic data.